(untitled) (Research, Society and Development, 2022)
This study aims to show how the theme music influences the choice of food by consumers, whether consciously or unconsciously, in addition to revealing how music exceeds the limits of sheet music, instruments and noise within the reach of a vibrational force that spreads throughout everywhere, exerting actions on the man which can be used in different occasions, mainly in the areas of food perception. The research was carried out through a bibliographic review with articles from more recent studies on the proposed theme in order to contribute to references to musical and mental effects. Several lines of research are based on experiments conducted with groups of people to demonstrate how the sound influence reflects on food consumption. These results reveal that music causes changes in our senses and mood, directly interfering with the taste and choice of food by the consumer.